2019
DOI: 10.1002/app.48631
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐clay nanocomposite hydrogels for molecular irrigation application

Abstract: Novel nanocomposite hydrogel pipes on the basis of polyvinyl alcohol and montmorillonite (MMT) clay were prepared via a cyclic freezing-thawing technique and designed for subsurface irrigation in the agricultural sector with extraordinarily reduced water consumption. The results showed that the prepared nanocomposite hydrogel pipes had an exfoliated morphology with improved mechanical and thermal properties. It was shown that the gel contents of nanocomposite hydrogel pipes were increased by increasing the loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…NC hydrogels have also been formed by mixing NCs directly into polymers. A cyclic freezingthawing process was recently used, where NC hydrogel pipes were prepared by loading montmorillonite (MMT) into a polyvinyl alcohol (PVA) matrix [65]. Another NC hydrogel made with this method was comprised of nano-ZnO loaded in poly(Nisopropylacrylamide-co-acrylic acid) (P(NIPAm-co-AAc)) using an in-situ process [66].…”
Section: Preparation Of Nanocomposite Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…NC hydrogels have also been formed by mixing NCs directly into polymers. A cyclic freezingthawing process was recently used, where NC hydrogel pipes were prepared by loading montmorillonite (MMT) into a polyvinyl alcohol (PVA) matrix [65]. Another NC hydrogel made with this method was comprised of nano-ZnO loaded in poly(Nisopropylacrylamide-co-acrylic acid) (P(NIPAm-co-AAc)) using an in-situ process [66].…”
Section: Preparation Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…For the PVA/MMT NC hydrogel pipes loaded with 10 wt % MMT, the ESR after 6 hours of drying was reduced by 25%. This may also be attributed to the increased crosslinking restricting the absorption of water molecules during the swelling processes [65].…”
Section: Determination Of Swelling Ratiomentioning
confidence: 99%
“…The enhancement of properties by NPs incorporation is due to either the ability of a group of NPs to act as charge carriers, electrooptically active centers, or as optical micro-cavities (Carter et al 1997). Various fillers materials were used for polymer nanocomposite preparation such as CNTs (Saeed and Khan 2014;Irzhak et al 2019), clay (Meneghetti and Qutubuddin 2006;Rezazadeh et al 2020), silica (Khdary and Abdelsalam 2020; Ibrahim and Sultan2020), graphene (Li et al 2016;Iniestra-Galindo et al 2019;Ovcharenko et al 2020) and metals NPs (Iwamoto et al 2003;Jadhav et al 2020;Ali et al 2014Ali et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoclay is a respectable applicant for the construction of organic-inorganic nanocomposites, since it can be destroyed to nano-platelets. [1][2][3][4][5][6][7][8][9][10] The polymer penetration into the clay galleries may cause the delaminated platelets (individual layers) or intercalated ones in the stacks with larger spacing among the platelets. [11][12][13][14][15] It was reported that the ion-exchange procedure by alkyl ammonium ions can enhance the hydrophobicity of clay surface and expand the clay packs, which enable the diffusion of polymer molecules into the clay channels.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoclay is a respectable applicant for the construction of organic–inorganic nanocomposites, since it can be destroyed to nano‐platelets 1–10 . The polymer penetration into the clay galleries may cause the delaminated platelets (individual layers) or intercalated ones in the stacks with larger spacing among the platelets 11–15 .…”
Section: Introductionmentioning
confidence: 99%